PROFANITY HAUNTS CHILDRENâS FIRST LANGUAGE ACQUISITION - Purnawan, Komang Gede (Lingual: Journal of Language and Culture, 2015)
This article aims at describing the phenomenon that more children use profanity or bad language nowadays and proposing a possible way to solve the problem. The materials for this article were the utterances of an eight-year-old boy in his interaction with adults in natural setting. The method of collecting data was by observation with recording technique. The collected data in the form of the transcription of the boyâs utterances were descriptively analyzed using ABC theory. The result shows that environment, like adults and mass media, have enormous impacts on childrenâs language